Comparison of Pregnancy Outcome between Elective and Emergency McDonald Cervical Cerclage in Cervical Insufficiency: 3-Year Experience (2006-2008) in Siriraj Hospital - Saifon Chawanpaiboon; Anuwat Sutantawibul (The Royal Thai College of Obstetricians and Gynaecologists, 2010)
Objective: To compare the pregnancy outcome between elective and emergency McDonald cervical cerclage in pregnant women with history or evidence of recurrent pregnancy loss by serial transvaginal ultrasound. Materials and Methods: During January 2006 and December 2008 (3 years), 14 pregnant women were included in the present study. All pregnant women were diagnosed of cervical insufficiency with history of recurrent pregnancy loss during 20-24 weeks of gestation. The first group included 6 pregnant women whom had been performed cervical cerclage during 14-16 weeks of gestation. The second group, included 8 pregnant women whom had been performed cervical cerclage after 16 weeks of gestation with the reasons of late visit and cervical length from serial transvaginal ultrasound lesser than 30 mm. Gestational age of delivery, complication and neonatal Apgar score were recorded. Results: All were performed McDonald cerclage. There was no statistical significance in maternal age, numbers of gravida, parity and abortion. There were significant differences in gestational age of delivery, mean Apgar score and mean neonatal birth weight in both groups. The complication of delivery in both groups was PPROM while placental abruption, PIH and preterm labour were founded in emergency cerclage group. Conclusion: The elective cervical cerclage performed during 14-16 weeks of gestation can prolong pregnancy longer and had better neonatal outcome compared with emergency cerclage performed after 16 weeks of gestation.